Targeted inhibition of the Plasmodium falciparum Vitamin B6 producing enzyme Pdx1 and the biochemical and functional consequences thereof - Birkholtz, Lyn-Marie (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.